PENGARUH TERAPI ACTIVE CYCLE OF BREATHING TECHNIQUE (ACBT) TERHADAP FREKUENSI PERNAFASAN (RESPIRATORY RATE) PADA PENDERITA TUBERKULOSIS PARU DI RUMAH SAKIT UMUM IMELDA PEKERJA INDONESIA MEDAN - Varida Naibaho, Eka Nugraha; Herlina Kabeakan, Sri Mega (Universitas Murni Teguh, 2021)
Pulmonary tuberculosis is a major public health problem in the world and is the second leading cause of death from infectious diseases. The purpose of this study was to determine the effect of active cycle of breathing technique (ACBT) therapy on breathing frequency in patients with pulmonary tuberculosis. Quantitative research method, with a Quasi Experimental research design with a pre-test and one-group post-test approach. The study was carried out in the Orchid room of the Imelda Indonesian Workers General Hospital in Medan in July - August 2021. The study population was 45 patients with pulmonary tuberculosis and the sample technique of this study was Nonprobability Sampling. The number of samples was 41 pulmonary tuberculosis patients according to the researcher's criteria. The data analysis technique used is Wilcoxon test analysis. The results of the study There was an effect of breathing patterns before the administration of active cycle of breathing technique (ACBT) Therapy on the improvement of respiratory frequency in patients with pulmonary tuberculosis with a value of M ± SD = 17.1081 ± 2.94188. There is an effect of breathing pattern after administration of active cycle of breathing technique (ACBT) Therapy on the respiratory frequency of Pulmonary Tuberculosis Patients with a value of M ± SD = 27.0400 ± 2.82076. There is a difference in the effect of breathing patterns before and after administration of active cycle of breathing technique (ACBT) therapy on the Improvement of respiratory frequency in pulmonary tuberculosis patients with a significant value of 0.000 < 0.005. Abstrak Tuberkulosis paru adalah masalah pokok kesehatan pada masyarakat didunia dan merupakan penyebab kematian ke dua dari penyakit infeksi. Tujuan penelitian untuk mengetahui pengaruh pemberian terapi active cycle of breathing technique (ACBT) terhadap frekuensi pernafasan pada penderita tuberkulosis paru. Metode penelitian kuantitatif, dengan desain penelitian Quasi Eksperiment dengan pendekatan pre test dan post test one group. Penelitian dilaksanakan di ruangan Anggrek Rumah Sakit Umum Imelda Pekerja Indonesia Medan pada bulan Juli - Agustus 2021. Populasi penelitian sebanyak 45 orang pasien Tuberkulosis Paru dan teknik sampel penelitin ini adalah Nonprobability Sampling. Jumlah sampel 41 orang pasien tuberkulosis paru sesuai dengan kriteria peneliti. Teknik analisa data yang digunakan adalah analisis uji Wilcoxon. Hasil penelitian ada pengaruh pola nafas sebelum pemberian terapi active cycle of breathing technique (ACBT) terhadap perbaikan frekuensi pernafasan pada penderita tuberkulosis paru dengan nilai M ± SD =17.1081 ± 2.94188. Ada pengaruh pola nafas sesudah pemberian terapi active cycle of breathing technique (ACBT) terhadap frekuensi pernafasan pasien tuberkulosis paru dengan nilai M ± SD = 27.0400 ± 2.82076. Ada perbedaan pengaruh pola nafas sebelum dan sesudah pemberian terapi active cycle of breathing technique (ACBT) terhadap perbaikan frekuensi pernafasan pasien tuberkulosis paru dengan nilai signifikan 0,000 < 0,005.